Les conjonctions parce que, car et puisque : retour sur les analyses antérieures et proposition d’un critère « attentionnel » - Lidia Lebas-Fraczak (Discours, 2024)
Most previous analyses of causal conjunctions parce que, car and puisque use an illocutionary criterion, opposing “explanation” and “justification”, and/or a presuppositional criterion. Other criteria are used to complete these analyses, such as the type of causality, the degree of subjectivity or the number of enunciation acts. We show through a review of the main contributions on the subject, that these various criteria have limits, giving rise to divergent analyses and failing to make a real functional distinction of the three morphemes. We hypothesize that such a distinction can be made by using a criterion of pragmatic and interlocutory nature, which can be considered as attentional, applying the notion of focusing.